Use of induced pluripotent stem cell derived neurons engineered to express BDNF for modulation of stressor related pathology - Liu, Gele; Rustom, Nazneen; Litteljohn, Darcy; Bobyn, Jessica; Rudyk, Chris; Anisman, Hymie; Hayley, Shawn (Frontiers in Cellular Neuroscience, 2014)
Combined cell and gene-based therapeutic strategies offer potential in the treatment of neurodegenerative and psychiatric conditions that have been associated with structural brain disturbances. In the present investigation, we used a novel virus-free re-programming method to generate induced pluripotent stem cells (iPSCs), and then subsequently transformed these cells into neural cells which over-expressed brain derived neurotrophic factor (BDNF). Importantly, the infusion of iPSC derived neural cells (as a cell replacement and gene delivery tool) and BDNF (as a protective factor) influenced neuronal outcomes Specifically, intracerebroventricular transplantation of iPSC-derived neural progenitors that over-expressed BDNF reversed the impact of immune (lipopolysaccharide) and chronic stressor challenges upon subventricular zone adult neurogenesis and the iPSC-derived neural progenitor cells alone blunted the stressor induced corticosterone response. Moreover, our findings also indicate that mature dopamine producing neurons can also be generated using iPSC procedures and these cells appeared to be viable when infused in vivo. Taken together, these data could have important implications for using gene-plus-cell replacement methods to modulate stressor related pathology.